Decision Making in the Process against Children Diversion Dealing with the Law Has not Aged 12 Years - Arya Yarsita, I Pande Ketut; Rodliyah; Cahyowati, RR. (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to examine and analyze the concept of decision making in the diversion process for children facing the law who are not yet 12 years old; and law enforcement decision making in the diversion process for children who are faced with a law that is not yet 12 years old (Study of the Chairperson of the Mataram District Court Number: 22/Pen.Div/2017/PN Mtr). The concept of decision making in the diversion process for children facing the law that is not yet 12 years old is the judge in imposing sanctions for children considering recommendations in the social research report made by community counselors to express and find data and information objectively about the development and background of life children from various sociological, psychological and other aspects while still paying attention to the best interests of the child. Law enforcement of decision making in the diversion process against children who are faced with a law that is not yet 12 years old emphasizes restorative justice which is the goal in the implementation of the diversion of cases of children facing the law. Law enforcement officials both Investigators, Community Guidance and Professional Social Workers conduct deliberations to reach a decision based on restorative justice that prioritizes the best interests of children.